(untitled) (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2023)
Every child deserves the opportunity to reach their full potential, yet gender inequalities prevalent in the lives of children in India impede this aspiration. Regardless of their geographical location within the country, children witness gender disparities in their homes, communities, media, and even among their caregivers. These inequalities are apparent in textbooks, films, and various media sources, as well as within the behaviors and attitudes of adults responsible for their care and support. The repercussions of gender inequality in India are reflected in unequal access to opportunities. Although both genders are affected by these inequalities, statistics indicate that girls are disproportionately disadvantaged. Globally, girls exhibit higher survival rates at birth, are more likely to achieve developmental milestones, and are equally inclined to participate in preschool programs. However, India stands out as the sole major country where the mortality rate of girls surpasses that of boys. Additionally, girls are more prone to dropping out of school. The experiences of adolescence are distinct for Indian girls and boys. While boys tend to enjoy greater freedom, girls encounter extensive limitations on their mobility and decision-making capabilities, particularly concerning work, education, marriage, and social relationships. As individuals mature, these gender-based barriers persist and extend into adulthood, resulting in a stark gender imbalance in the formal workforce, with only a quarter of women participating. While certain Indian women have achieved global recognition as leaders across diverse fields, the majority of women and girls in India remain deprived of many of their rights due to deeply ingrained patriarchal norms, traditions, and social structures. Consequently, girls face inherent risks, vulnerabilities, and violations solely due to their gender. These risks are closely intertwined with the economic, political, social, and cultural disadvantages that girls encounter daily, exacerbating further during crises and disasters. Gender discrimination and prevailing social norms and practices subject girls to the potential hazards of child marriage, adolescent pregnancy, domestic child labor, inadequate education and healthcare, sexual abuse, exploitation, and violence. These critical issues are unlikely to change unless society places greater value on the well-being and rights of girls.